633. Eravacycline Use in Immunocompromised Patients: Multicenter Evaluation of Clinical and Safety Endpoints. (15th December 2022) - Kunz Coyne, Ashlan J; Allosaimy, Sara; Molina, Kyle C; Kang-Birken, Lena; Lagnf, Abdalhamid M; Claeys, Kimberly C; Veve, Michael; King, Madeline; Pullinger, Benjamin; Bouchard, Jeannette; Gore, Tristan; Rojas, Leonar; et al.
Abstract: Background: Infections caused by multidrug-resistant (MDR) bacteria are an increasingly common public health threat associated with worse outcomes in immunocompromised patients. Eravacycline (ERV) has potent in-vitro activity against MDR Gram-negative and Gram-positive bacteria and has demonstrated non-inferiority to meropenem in the phase III IGNITE4 trial; however, the trial excluded immunocompromised patients. We aimed to evaluate clinical and safety endpoints of immunocompromised patients receiving ERV as definitive therapy. Methods: Multicenter, retrospective, observational study conducted from October 2018 to April 2022. Adult hospitalized immunocompromised patients treated with ERV for ≥72 hours were included. Immunocompromised patients were defined as having any of the following: chemo or radiation therapy < 30 days of hospital admission, HIV/AIDS with CD4 < 200, chronic steroids ( >40 mg prednisone or equivalent. The primary outcome was 30-day survival. Secondary outcomes were lack of 30-day infection recurrence and drug-related safety events. Results: Overall, 75 immunocompromised patients treated with ERV were included from 17 United States medical centers. Median (IQR) age was 62 (53-70) and 61.6% were male. Hospital length of stay was 28 (13-42) days and 67% were admitted to the intensive care unit. SOFA and APACHE II scores were 3.5 (1-7) and 16 (11-20), respectively. Common infection sources were intra-abdominal (26%) and lower respiratory tract (18%); 24% were bacteremic. Most patients had cultured Enterobacterales (58.7%) and Enterococci (37%) spp. infections. Of those, 21.3% were CRE and 19% were VRE. Infectious diseases consult was obtained in 91.8% of cases. Time elapsed from index culture collection to ERV initiation was 4 (2-8) days and duration of ERV therapy was 7 (4-12) days. In total, 81.3% of immunocompromised patients achieved 30-day survival and 90.7% did not have 30-day infection recurrence. Probable drug-related adverse events occurred in 5.3% of patients (GI 4%, rash 1%). Conclusion: A majority of immunocompromised patients receiving ERV as definitive therapy achieved 30-day survival and did not experience infection recurrence. ERV use in immunocompromised subpopulations will benefit from studies tailored to their specific characteristics. Disclosures: Kimberly C. Claeys, PharmD, BioFire Diagnostics: Honoraria Bruce M. Jones, Pharm.D., FIDSA, BCPS, AbbVie: Advisor/Consultant|AbbVie: Honoraria|La Jolla: Honoraria|Melinta: Advisor/Consultant|Paratek: Honoraria|Regeneron: Honoraria.